# Category Archives: Trigonometry

# Cosine Rule Transformation

# Sine Rule Derivation

Use the formulas you’d use to calculate the area of a triangle. See the magic emerge.

# Trigonometric Proofs

Rules:

Transformation 1:

Transformation 2:

# Derivative of y=cotx

# tan(A-B)=(tanA-tanB)/(1+tanAtanB)

Prove that:

Firstly:

Also, remember that:

So:

# Derivate Of y=cosx Proof

Prove that:

# sin(A-B)=sinAcosB-cosAsinB

Prove that:

# tan(A+B)=(tanA+tanB)/(1-tanAtanB)

Prove that:

# Simple But Elegant Way To Prove That sin(A+B)=sinAcosB+cosAsinB (Edexcel Proof Simplified)

Learn why sin(A+B)=sinAcosB+cosAsinB with this elegant proof…

**Like this proof? Why not check out this page…**

How to prove that sin(A-B)=sin(A)cos(B)-cos(A)sin(B) geometrically